Sophie Ristelhueber - Hindry, Ann (Paris : Editions Hazan Paris, 1998)
Sophie Ristelhueber is concerned, first and foremost, with the ambivalence of things, the porous borderline between reality and fiction, the dialectical relationship between words and image, and the variable hierarchy of figures of speech, be it iconographic or linguistic speech : the said and the unsaid, more for less, part for whole. Trained in the nominalist enumeration of the Nouveau Roman (once the subject of her essay) Sophie Risterhueber explores the crannies and confines of the iconic field - of what makes imagery - with her invariably sober and discreet approach.
bibliog., T.V., filmog. p. 107-109
biog., ind. tent., gr. tent. p. 105-106
Engels
Frans
boek
Keywords: Ristelhueber, Sophie